Using Magnetic Field Gradients to Shorten the Antigen-Antibody Reaction Time for a Magnetic Immunoassay - Tsukada, Keiji; Tsunashima, Kenta; Jinno, Katsuya; Hiramatsu, Bunta; Takeuchi, Shun; Fujimoto, Kayo; Kenji, Sakai; Kiwa, Toshihiko; Mohd Mawardi, Saari (IEEE, 2019)
The measurement of biological targets using nanoparticle magnetic markers has been extensively studied for its applications in magnetic immunoassays (MIAs). Compared with the optical immunoassay method, the MIA methods have some attractive characteristics such as a wash-free process that does not need bound/free marker separation and the ability to detect biological targets in a nebulous liquid. In addition, the wash-free process is very fast. In this paper, we tried to reduce the reaction time for the antigen-antibody reaction in order to make the MIA method more attractive. The reduction in reaction time and the detection characteristic of biological targets were demonstrated using C-reactive proteins (CRPs) as biological targets for diagnosing inflammation. To shorten the reaction time, a magnetic-shaking method using the magnetic field gradient from a neodymium magnet was developed. When comparing the reaction times with and without magnetic shaking, it was found that the reaction time decreased with magnetic shaking for all CRP concentrations. Even after the magnetic-shaking treatment, the dependence of the CRP concentration on the magnetic signal was observed. The number of surface modifications per magnetic marker and the magnetic marker concentration also affected the reaction time. In order to obtain the desired measurement range based on the CRP response characteristic, it is necessary to optimize the number of magnetic markers and polymer beads used.